Design, synthesis and in-vitro evaluation of fluorinated triazoles as multi-target directed ligands for Alzheimer disease. (15th June 2021) - Dalvi, Tanay; Dewangan, Bhaskar; Agarwal, Gopal; Shinde Suchita, Dattatray; Jain, Alok; Srivastava, Akshay; Sahu, Bichismita
Graphical abstract: Multi-target directed hexaflourocarbinol containing traizole amides and amines were designed by de-novo approach which can inhibit Aβ peptide aggregation by blocking the aggregation prone core, chelate with the excessive metals and reducing the ROS by scavenging. Novel fluorinated triazole compounds were found to inhibit Aβ aggregation, chelate biometals (Cu, Zn and Fe) and demonstrate ROS scavenging ability. Abstract: Alzheimer disease is multi-factorial and inflammation plays a major role in the disease progression and severity. Metals and reactive oxygen species (ROS) are the key mediators for inflammatory conditions associated with Alzheimer's. Along multi-factorial nature, major challenge for developing new drug is the ability of the molecule to cross blood brain barrier (BBB). We have designed and synthesized multi-target directed hexafluorocarbinol containing triazoles to inhibit Amyloid β aggregation and simultaneously chelate the excess metals present in the extracellular space and scavenge the ROS thus reduce the inflammatory condition. From the screened compound library, compound 1c found to be potent and safe. It has demonstrated inhibition of Amyloid β aggregation (IC50 of 4.6 μM) through selective binding with Amyloid β at the nucleation site (evidenced from the molecular docking). It also chelate metals (Cu +2, Zn +2 and Fe +3 ) and scavenges ROS significantly. Due to the presence of hexafluorocarbinol moiety in the molecule it may assist to permeate BBB and improve the pharmacokinetic properties. The in-vitro results of compound 1c indicate the promiscuity for the development of hexafluorocarbinol containing triazoles amide scaffold as multi-target directed therapy against Alzheimer disease.